A New Application in Biology Education: Development and Implementation of Arduino-Supported STEM Activities - Gorgulu Ari, Asli; Meco, Gulsum (MDPI, 2021)
Simple Summary The rapid increase in technology in recent years has created the need to apply different methods in education. Teaching lessons with technology-based activities rather than the traditional teaching method is an obligation for teachers. For this reason, teachers need resources whose validity and reliability are tested that they can use in their lessons. In this study, a part of the technology content resource that teachers need for a biology lesson is presented. While preparing the course contents, a STEM approach including science, engineering, mathematics and technology disciplines was used. A significant increase was found in the ability of the students to whom the developed activities were applied to establish cause and effect relationships. According to this result, it can be said that Arduino-supported STEM education improves students' abilities to establish cause and effect relationships. Considering that generations that have grown up in the 21st-century have grown alongside technology, it is thought that integrating technology into lessons helps students learn the subject. This study aims to develop five STEM activities for the lesson of the human body systems by integrating the coding-based Arduino into STEM education. The activities were implemented to 6th-grade students for seven weeks and the effects on students' skills of establishing a cause-effect relationship. The study method was pre-test-post-test quasi-experimental design, and the cause-effect relationship scale and semi-structured view form were used as data collection tools. As a result of the study, a significant difference was found between the Arduino-supported STEM activities developed and the students' skills of establishing a cause-effect relationship. The students who received the Arduino-supported STEM education found the course to be entertaining and educational, and the future goals of these students were affected. In order to bring individuals who love their profession into the future, Arduino-supported STEM education should be applied and expanded in other branches and class levels.
Keywords: Arduino; 21st century skills; thinking skills; computational thinking; critical thinking; STEM; LEARNING ANALYTICS; CHALLENGES; Life Sciences & Biomedicine - Other Topics